Error-Resistant Adaptive Filtering for INS/SAR Integrated Navigation System - Shesheng Gao; Yalin Jiao; Yu Gu; Yongmin Zhong (2009 2nd International Congress on Image and Signal Processing, 2009)
This paper presents a new error-resistant adaptive filtering algorithm for INS/SAR (Inertial Navigation System / Synthetic Aperture Rader) integrated navigation system. This algorithm adopts the principle of error-resistant estimation to adaptively process measurement information. The experimental results demonstrate that the performance of the proposed error-resistant adaptive filtering algorithm can significantly improve the performance of INS/SAR integrated navigation system.